Obesidade na infância no contexto sociofamiliar: possibilidades de (des)construção e (res)significação de identidades (pré-)escritas - Valeria Tassara (2006)
This paper presents an in-depth study of childhood obesity in a social and familial context. According to the bibliography presented, most studies of this topic are of a quantitative nature, with emphasis on descriptive aspects and statistics. We observed four children, two boys and two girls, who received a medical diagnosis of obesity, as well as their families (father, mother and siblings). The children were between the ages of 7 and 12, and were patients of the Pediatric NutritionalDisturbance service at the Federal University of Minas Gerais. The theoretical and methodological rationales for this study were based on the perspectives of the Systemic and Complexity theories. To this end, the following instruments were used: in-depth interviews with fathers and mothers; genograms with family members and body image drawings with the children. The analysis and interpretation of the data was grounded on a systemic structure, which took the complex nature of the problem into account, and uncovered relevant indicators. Among these indicators were family secrets about the stories surrounding parental figures; the complicated relationship between mothers/sons and daughters that indicated a certain distance between parents with respect to the children; biological and symbolic transgenerational phenomena of obesity in three generations of family groups studied; as well as familymyths and loyalties, which are a basis of personal and family identity of the overweight individual. These signals were fundamental to understanding the difficulties involved in the process of differentiation of these children, that is, the possibility of weight loss being experienced, in a veiled way, as a threat to the identity processes of the family group, as demonstrated in their body image drawings. From this perspective, the study showed that the interactions between fathers, mothers,sons and daughters, which are permeated with suffering, conflicts, values and beliefs, are linked to biological, nutritional and psycho-social issues that involve the family dynamics of the subjects studied. Finally, we observed the fundamental importance of placing childhood obesity in context, shifting the focus of responsibility for the problem away from the child, and including it in the socio-familial context. This study indicated other possibilities for intervention, and highlighted the importance of an interdisciplinary approach for professionals who treat childhood obesity.